Complex Relationships of Smoking, HLA–DRB1 Genes, and Serologic Profiles in Patients With Early Rheumatoid Arthritis: Update From a Swedish Population‐Based Case–Control Study. Issue 9 (24th July 2019) - Hedström, Anna Karin; Rönnelid, Johan; Klareskog, Lars; Alfredsson, Lars
Abstract : Objective: Smoking is associated with an increased risk of rheumatoid arthritis (RA) in subsets of patients defined according to the presence or absence of anti–citrullinated protein antibodies (ACPAs) and rheumatoid factors (RFs). Moreover, an interaction between smoking and the HLA–DRB1 shared epitope (SE) has been demonstrated to be a risk factor for seropositive RA. The aim of this study was to investigate the interplay between smoking and the HLA–DRB1 SE with regard to risk of RA in different patient subsets based on ACPA and RF status. Methods: Incident cases of RA (3, 645 cases, 5, 883 matched controls) were divided into 4 subgroups based on the presence or absence of RF and anti–cyclic citrullinated peptide 2 (anti‐CCP2) antibodies. The influence of smoking on the risk of disease was determined in each RA subgroup, using logistic regression models with calculation of odds ratios and 95% confidence intervals (95% CIs). The potential interaction between smoking and HLA–DRB1 SE genes was evaluated by calculating the attributable proportion due to interaction (AP). Results: In the RF+/anti‐CCP2+ subset of RA patients, both smoking and the presence of the HLA–DRB1 SE conferred independent disease risks, and there was a strong interaction between the 2 risk factors (AP 0.4, 95% CI 0.3, 0.5). In the RF−/anti‐CCP2+ patient subset, the HLA–DRB1 SE conferred an increased risk of RA, whereas the independent influence of smoking was limited. However, there was a significant interaction between the HLA–DRB1 SE and smoking (AP 0.2, 95% CI 0.02, 0.5). In the RF+/anti‐CCP2− patient subset, there was an increased risk of disease among smokers, which was only marginally affected by the presence of the HLA–DRB1 SE, and no interaction between the 2 factors was observed (AP 0.002, 95% CI −0.3, 0.3). In the RF−/anti‐CCP2− patient subset, neither smoking nor the presence of the HLA–DRB1 SE conferred an increased risk of RA. Conclusion: These findings demonstrate different effects of smoking and HLA–DRB1 in the 4 serologically defined RA subsets.